Analysis of Off-Street Parking Capacity at Cirebon Super Block, Cirebon City - Fauzan Akbar Gumilang; Suhar Adi Saputra; Zulkifli Zulkifli; Shinta Novriani; Herry Hermawan (Journal of World Science, 2024)
Rapid population growth and economic progress have increased the need for public facilities such as shopping malls, hospitals, and office buildings. Cirebon Super Block (CSB) is one of the shopping centers in Cirebon City that adopts the 4-in-1 concept. However, CSB faced problems in providing adequate parking facilities, causing vehicle congestion at the mall entrance and traffic jams. This study aims to identify existing parking conditions, analyze the need for parking spaces, and provide technical recommendations to increase the availability of parking spaces in CSB. This study uses quantitative methods with primary and secondary data collection. The results of the study show that CSB has an off-street parking capacity of 808 SRP (standard parking spaces) for cars and 1188 SRP for motorcycles. The analysis shows that the highest parking index for cars occurred on Saturday reaching 101%, with the highest accumulation of 750 vehicles, the volume of 1011 vehicles, and the average parking duration of 1.75 hours. The highest parking index for motorcycles also occurred on Saturday reaching 91.1%, with the highest accumulation of 1082 vehicles, the volume of 1855 vehicles, and the average parking duration of 2,088hours. The implication of this study is to plan the construction of a parking building on the west side using Civil 3D software and convert an area of 720m² from 26 SRP to 111 SRP. This recommendation is expected to increase the parking capacity from 818 SRP to 918 SRP, so that it can reduce congestion and improve the comfort of CSB visitors.